PENGARUH SUPERVISI KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SD DI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Vera Viani; Caska Caska; Daeng Ayub (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
The purpose of this study was to determine the effect of principal supervision and work motivation on the performance of elementary school teachers in Bangko District, Rokan Hilir Regency. The phenomenon that occurs is that few teachers feel that supervision is a service need for the development of their potential and professionalism. Another phenomenon is the lack of maximum educational services because teachers are less aware of their main duties as teachers. This can be seen from the unsteady preparation of teaching, monotonous learning methods, the lack of use of IT-based media and the MGMP has not been running effectively to improve the competence of the sustainability professional development program and teacher performance in the MGMP/KKG and MKKS forums. This type of research is descriptive quantitative research. The data collection technique is a questionnaire given to 93 teachers who were chosen randomly as a sample using the census sampling method. The research was carried out, namely the respondents gave responses to the questionnaire in the form of a Likert scale. The data analysis technique used in this study is multiple linear regression and data processing using the Statistical Package for Social Science (SPSS) program. Based on the results of the research, the principal's supervision affects the teacher's performance by 19.3%. Based on the results of the statistical test results of t work motivation on teacher performance, the t-count value is 2.733. Thus, t count is greater than t table (2.308 > 1.662) as shown in the table above, and the value is 0.023 < 0.05. Thus, t count is in the area where Ho is rejected and Ha is accepted, meaning that partially the higher the level of work motivation, the performance of the teacher will increase. The results of research on work motivation show that work motivation affects teacher performance, meaning that the better the work motivation, the better the teacher's performance. This means that the principal's supervision and work motivation are important variables to improve teacher performance. The better the principal's supervision, work motivation, the better the teacher's performance.